Exploring the role of English club for students' speaking skills - Romli, Siti Sarah Herlina; Yanie, Kayla Hannifa Dwi; Safhira, Nadia Indah; Rohimah, Imas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study explores the role of English clubs in improving the speaking skills of junior high school students. By utilizing a descriptive qualitative approach, data was collected through observation and semi structured interviews with nine participants from a public junior high school in Bandung, Indonesia. The result showed that enrollment in the English club can improve students’ confidence and speaking skills, including vocabulary, pronunciation, grammar, and fluency. The encouraging environment and engaging activities, such as public speaking, storytelling, and watching English movies, created a comfortable learning atmosphere. The teacher plays an important role providing constructive feedback, which motivates students to develop without fear of making mistakes. Collaboration with peers cultivates a positive learning environment. Apart from these benefits, challenges such as repetitive material and short duration of participation were also noted. The study concludes that English clubs effectively enhance speaking skills by combining interactive activities, teacher coaching, and peer support. The study also recommends integrating English clubs into school programs and carrying out further research on long term impact and wider application, including the use of digital tools to improve engagement and learning outcomes.